Evaluación de la influencia del conocimiento ambiental en las capacidades locales de la parroquia Membrillo - Avellán Vera, Eddy Francisco (2015)
The research was to evaluate the influence of environmental knowledge in local capabilities Qunce parish. The applied research was not experimental. For the diagnosis of environmental knowledge the method of participatory action research, for capacity assessment methodology United Nations Program was used was used. Diagnostic results showed that environmental awareness on environmental problems identifies are not only development, but basically of wnowledge and education, beyon learning about the environment, related the undestanding and address, which are still insufficient knowledge and actions that are performed locally, to stop or eliminate these environmental problems affecting the community, by human action. The capacity assessment was the starting point for formulating a response to capacity development.Through environmental education proposal implemented, same as performed activities for children, leaders and community members, ensuring that all citizens and everyday activities the environment and its protection, to provide a sustainable and economically sustainable economic and social development to be present. We conclude that knowledge related to environmental awareness, operation and environmental issues.